DOMAIN NAME PROTECTION IN SOUTH AFRICA - Frans E Marx (Obiter, 2023)
This paper investigates the legal mechanisms that are available when one is dealing with domain name disputes. It describes the domain name system and contrasts this with other forms of intellectual property. The different types of domain name conflicts are discussed and the legal measures available for protection of domain names as intellectual property are highlighted. Reference is made to national protection measures such as the Trade Marks Act 194 of 1993 and common law protection of intellectual property. Certain international legal mechanisms such as the World Intellectual Property Organisation’s rules with regard to online domain name dispute resolution and the United State’s Anticybersquatter Consumer Protection Act of 1999 are also discussed as these measures have a direct influence on some domain names of South African businesses. Lastly the changes to domain name dispute resolution procedures envisaged by the Electronic Communications and Transactions Act 25 of 2002 are discussed. Since the advent of e-commerce a new species of highly valuable intellectual property has developed. Although there are remarkable similarities between domain names and “common law trade marks” and trade marks protected by the Trade Marks Act 194 of 1993 there are also important differences, which cause uncertainty and confusion when disputes involving domain names arise. These differences flow mainly from the unique characteristics of domain names. The purpose of this note is to investigate the domain name system as it is used in South Africa, to compare domain names and trade marks, and to look at the protection mechanisms which an aggrieved party may have at his or her disposal if he should find that his business name or trade mark (or something similar) is being used by a domain name registrant in a way that conflicts with his interests. In addition, a short comparison of how these problems are addressed by the international community, particularly the USA and Britain, will be made.